Enhancing Patient Revisit Intention and Positive Word of Mouth: An Empirical Study of Medical Tourism - Timothy Demas Mandita Putra; Nisfu Laili Romadhona; Tengku Mohd. Khairal Abdullah (University of Merdeka Malang, 2024)
The growth of medical tourism industry in various countries has fostered global competition. Hospitals need to improve healthcare quality, brand image, and perceived value to gain patient satisfaction so that there is an increase in positive word-of-mouth and patient revisit intention. Therefore, it is necessary to study the behavior of patients visiting abroad to get health services and the desire to recommend the goodness of the hospital. This study aims to analyze the impact of hospital brand image, service quality, and perceived value to increase patient satisfaction. It also examines the impact of patient satisfaction on positive word-of-mouth and revisits intention. This study uses a quantitative method with a survey approach to 130 patients overseas for health services. Therefore, the convenience sampling method was applied in this study. Variance-based Structural Equation Modeling technique was used to answer the research hypotheses. The results have proven that to increase patient revisit intention in hospitals and positive WoM, the hospital must pay attention to service quality, hospital brand image, and perceived value need to be considered as they impact patient satisfaction. Meanwhile, patient satisfaction was identified as a factor that drives positive word-of-mouth and patient revisit intention.